2005
DOI: 10.1007/s00216-005-3389-8
|View full text |Cite
|
Sign up to set email alerts
|

Matrix effects during phosphorus determination with quadrupole inductively coupled plasma mass spectrometry

Abstract: A quadrupole inductively coupled plasma mass spectrometer was evaluated for use in the detection of phosphorus. The influences of nitric acid and methanol (simulating the composition of a sample solution after nitric acid digestion) on phosphorus determination were studied using two different measuring methods at different plasma conditions: detection of phosphorus ions at m/z 31 and detection of phosphorus oxide ions at m/z 47. The existence of polyatomic interferences at m/z 31 and 47 was explored. Nitric ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 17 publications
2
29
0
Order By: Relevance
“…Be, Se, As, Au, I, P, S,…) were higher than those of elements with about the same mass/charge ratio and low IPs values. Similar results have been reported by other authors [16][17][18][19]. Thus, Allain et al [16] reported a signal enhancement for Hg (600%), As (240%), Au (325%) and Se (250%) when a 36 g L − 1 carbon (as glycerol) solution was introduced into the ICP-MS. To explain these findings, some authors suggested a charge transfer mechanism between the analyte atoms and carbon positively charged ions [20,21].…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Be, Se, As, Au, I, P, S,…) were higher than those of elements with about the same mass/charge ratio and low IPs values. Similar results have been reported by other authors [16][17][18][19]. Thus, Allain et al [16] reported a signal enhancement for Hg (600%), As (240%), Au (325%) and Se (250%) when a 36 g L − 1 carbon (as glycerol) solution was introduced into the ICP-MS. To explain these findings, some authors suggested a charge transfer mechanism between the analyte atoms and carbon positively charged ions [20,21].…”
Section: Introductionsupporting
confidence: 86%
“…For higher carbon concentrations, interferences are more pronounced [16,22]. Similar behavior was obtained using other carbon sources such as acetic acid [23], acetone [15,24], alcohols [18,22], ethylendiamine [25], ammonium carbonate [26] or methane [27].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Generally speaking, the enhancement factors of As and Se reported in the literature for non-volatile carbon sources (glucose, citric acid, oxalic acid or glycerol) were always lower than for more volatile reagents such as methanol or even for gases (CH 4 ), both in ICP-OES 3,10,11 and in ICP-MS. 1,2,4,6,7,9,[13][14][15]…”
Section: Effect Of Phenylalanine and Comentioning
confidence: 99%
“…Rodushkin et al 6 had reported that the analytical performance of ICP-SFMS was significantly improved by addition of methane to the argon gas flow, the signal intensities of As, Te, Se and Sb were enhanced two-to four-fold. Kovacevic et al 7 studied the matrix effect of methanol on ICP-MS signals of phosphorus, a sevenfold increase in the phosphorus signal was observed when water and 2.5 mol L -1 methanol were compared.…”
Section: Introductionmentioning
confidence: 99%